Meat processing : improving quality - Kerry, Joseph (Microbiologist); Kerry, John; Ledward, David (CRC Press ; Woodhead Pub., 2002)
Annotation CONTENTS Defining meat quality. Part 1 Analysing meat quality: Factors affecting the quality of raw meat; Nutritional quality of meat; Lipid-derived flavours in meat products; Modelling colour stability in meat; Fat content of meat and meat products. Part 2 Measuring quality: Quality indicators for raw meat; Sensory analysis of meat; On-line monitoring of meat quality; Microbiological hazard identification in the meat industry. Part 3 New techniques for improving quality: Modelling beef cattle production to improve quality; New developments in decontaminating raw meat; Automated meat processing; New developments in the chilling and freezing of meat; High pressure processing of meat; Processing and quality control of restructured meat; Quality control of fermented meat products; Quality control of low-fat meat products; New techniques for analysing raw meat; Meat packaging.
Keywords: Meat -- Quality.; Meat industry and trade -- Quality control.; elektronické knihy; electronic books